2021
DOI: 10.3390/jcm10112248
|View full text |Cite
|
Sign up to set email alerts
|

Circulating PTGS2, JAG1, GUCY2C and PGF mRNA in Peripheral Blood and Serum as Potential Biomarkers for Patients with Metastatic Colon Cancer

Abstract: Genes involved in the angiogenic process have been proposed for the diagnosis and therapeutic response of metastatic colorectal cancer (CRC). This study aimed to investigate the value of PTGS2, JAG1, GUCY2C and PGF-circulating RNA as biomarkers in metastatic CRC. Blood cells and serum mRNA from 59 patients with metastatic CRC and 47 healthy controls were analyzed by digital PCR. The area under the receiver operating characteristic curve (AUC) was used to estimate the diagnostic value of each mRNA alone or mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…A study by Pun et al [ 110 ] has revealed that plasma levels of the Bmi1 transcript may be used as a biomarker in mCRC patients for non-invasive monitoring of occult metastases and anticipating the emergence of distant metastases. mRNA produced from the genes prostaglandin-endoperoxide synthase 2 ( PTGS2 ), guanylate cyclase 2C ( GUCY2C ) and jagged canonical notch ligand 1 ( JAG1 ) were reported to be upregulated in mCRC, while the serum expression of GUCY2C and GUCY2C/PTGS2 showed correlation with the therapeutic response [ 111 ]. However, a definitive prognostic cf-mRNA biomarker for response to therapy and survival of mCRC patients has yet to emerge.…”
Section: Cell-free Nucleic Acids As Crc Biomarkersmentioning
confidence: 99%
“…A study by Pun et al [ 110 ] has revealed that plasma levels of the Bmi1 transcript may be used as a biomarker in mCRC patients for non-invasive monitoring of occult metastases and anticipating the emergence of distant metastases. mRNA produced from the genes prostaglandin-endoperoxide synthase 2 ( PTGS2 ), guanylate cyclase 2C ( GUCY2C ) and jagged canonical notch ligand 1 ( JAG1 ) were reported to be upregulated in mCRC, while the serum expression of GUCY2C and GUCY2C/PTGS2 showed correlation with the therapeutic response [ 111 ]. However, a definitive prognostic cf-mRNA biomarker for response to therapy and survival of mCRC patients has yet to emerge.…”
Section: Cell-free Nucleic Acids As Crc Biomarkersmentioning
confidence: 99%
“…As was mentioned above, the SW620-EVs significantly promoted the migration of HUVECs; therefore, we conducted RT-PCR for tumor-related mRNA screening of SW480-EVs and SW620-EVs and also detected EVs isolated from cell medium of human primary CRC cells HCT116 (HCT116-EVs) to achieve a more accurate differential expression analysis. As shown in Figure 5a, some upregulated mRNAs in the SW620-EVs have been reported to be involved in CRC angiogenesis, including ADM, 34,35 BPTF, 36 FZD5, 37,38 ID1, 39 JAG1, 40,41 PGF, 42 and PIK3C2A. 43,44 In addition, FAM83D, 45 LPR1, 46 and YWHAZ, 47 which were more highly expressed in SW620-EVs than in SW480-EVs and HCT116-EVs, were also closely related to tumor development (Figure S7).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Of note, this ligand was recently introduced as a new high-affinity ligand for DC-SIGN, a basic receptor of the innate immune system ( Krylov et al, 2023 ). Due to the low sensitivity and specificity of existing screening methods, much effort is focused on finding new potential biomarkers for colon cancer ( Jimenez-Luna et al, 2021 ). Tumor and normal tissues are characterized by different glycosylation profiles ( Zhao et al, 2018 ); in particular, high-mannose N-glycans are regarded as markers of malignant progression in the early stages of colorectal cancer ( Boyaval et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%